2022
DOI: 10.20937/atm.52895
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability assessment studies on climate change: a review of the research in Mexico

Abstract: Highlights • Research should be increased about protected areas, soil, health, and tourism. • Northern and central Mexico's regions are the zones with the least number of studies. • Exist differences in the conceptualization of exposure in the vulnerability formula. • We found 21 different methods used to assess vulnerability to climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…We also have yet to examine CC’s effect on species habitats. For example, pollution, sea-level rise, and many other factors further impact marine organisms in Mexico [20]. Thus, the alterations via CC probably may be more pronounced than what has been predicted in this work.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We also have yet to examine CC’s effect on species habitats. For example, pollution, sea-level rise, and many other factors further impact marine organisms in Mexico [20]. Thus, the alterations via CC probably may be more pronounced than what has been predicted in this work.…”
Section: Discussionmentioning
confidence: 79%
“…Studies relating to species vulnerability in Mexico are scarce making our results harder to compare since most studies are usually at a regional scale [15,[69][70][71][72]. Even so, a few studies have tried to predict the vulnerabilities of fisheries throughout the country [18,20]. This study found spatial patterns of changes in suitability, ecological richness, and turnover through the climate change scenarios; however, their magnitude was related to the warming degree.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to national and international reviews [5,6], territories as a category of geographic analysis are one of the most recurrent subjects in climate change vulnerability studies (e.g., towns, cities, municipalities, countries, watersheds, physiographic regions, and natural protected areas).…”
Section: Introductionmentioning
confidence: 99%
“…These studies evaluate how the different elements in the territory (e.g., physical, biotic, human, and cultural) may be affected by climate change, in order to propose territorial action strategies that minimize damage [7]. Describing the exposure component is one of the challenges of vulnerability studies, especially in studies of territories where the exposed system is the geographic landscape [6].…”
Section: Introductionmentioning
confidence: 99%